Autohydro Therapy Reducing Blood Glucose Levels in Type 2 Diabetes Mellitus Patients - Nian Afrian Nuari; Efa Nur Aini (Lembaga Pengembangan Kinerja Dosen, 2024)
Hyperglycemia is a blood glucose level that contains a lot of sugar in the body's blood circulation. Autogenic relaxation can control blood glucose in the body, by thinking about the feeling of warmth and heaviness in the body parts. Water therapy (Hydrotherapy) is a method of treatment and healing using water as a medium. The aim of this study was to determine the effect of Autohidro (autogenic relaxation therapy and water therapy (Hydrotherapy) on blood glucose in patients with type II diabetes mellitus. The research design used Quasy Experimental with a pre test and post test control group approach, using a purposive sampling technique to obtain samples 32 respondents consisting of 16 people in each group, both control and treatment groups. Data processing and data analysis using the Paired T-Test and Independent T-Test. Results of data analysis using the Paired T-Test, Blood glucose in Diabetes Mellitus respondents there was a difference in the intervention group (p value 0.023), while in the control group there was no change in blood glucose (p value 0.064). Based on analysis using the Independent T-Test, it showed that there was an effect of Autohidro therapy on the blood glucose of Type II Diabetes Mellitus patients (p value 0.022). Autohidro therapy can be an alternative therapy to reduce blood glucose levels in Type II Diabetes Mellitus patients.